The Relationship Between Nurse’s Knowledge about Ventilators and Compliance in Preventing Ventilator - Associated Pneumonia (VAP) in the ICU - Tri Wahyuni; Viyan Septiyana Achmad; Rahmat Pannyiwi; Rezqiqah Aulia Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Ventilator Associated Pneumonia (VAP) is one of the most common nosocomial infections in ICU patients and has the potential to increase morbidity, mortality, and cost of care. Nurses' compliance with VAP prevention protocols is greatly influenced by their knowledge of ventilators and related nursing practices. This study aims to analyze the relationship between nurses' knowledge of ventilators and their compliance in VAP prevention in the ICU. This study was an observational study with a cross-sectional design. The sample consisted of 60 ICU nurses selected purposively in three hospitals in city X. Data were collected using a ventilator knowledge questionnaire and VAP prevention compliance observation. Data analysis used the Pearson correlation test to determine the relationship between knowledge and compliance. The results showed a significant positive relationship between nurses' knowledge level about ventilators and compliance in VAP prevention (r = 0.58; p < 0.01). In conclusion, increasing nurses' knowledge regarding ventilators has an effect on improving VAP prevention compliance. It is recommended that hospitals regularly conduct training and education for ICU nurses to improve nosocomial infection prevention practices.